A Bibliometric Analysis of Augmented Reality and Virtual Reality During 1993–2022 - Hamdan Gani; Muhammad Ibrar Aprianto (JEAT : Journal of Electrical Automation Technology, 2023)
Augmented reality (AR) and virtual reality (VR) have received much attention recently as innovative and valuable technology. With the growth of AR and VR research, a comprehensive examination is required. From the standpoint of bibliometrics, this study conducts a comprehensive analysis of AR and VR papers from 1993 to 2022. A total of 6,785 publications are obtained from the Web of Science (WoS) database and loaded into the professional science mapping tools VOSviewer and Cite Space through preprocessing. The publishing structures are examined using annual publications and the publications of the most productive countries/regions, institutions, and authors. Afterward, the co-citation networks of countries/regions, institutions, authors, and articles are visualized using VOSviewer. Their citation structure and the most influential examples are investigated further. Finally, VOSviewer depicts the collaboration networks of countries/regions, institutions, and writers. Cite Space utilizes timeline analysis and keyword citation burst detection to identify hotspots and research trends. Finally, this study explains a basic understanding of AR and VR for scholars and a detailed examination of AR and VR for future research in this area.